Small-signal modeling and wide-band oscillation analysis with the high proportion of renewable energy integrated through LCC-HVDC - Jiang, Kezheng; Liu, Dan; Cao, Kan; Hu, Pan; Xiong, Ping; Wu, Yingzi (Frontiers in Energy Research, 2023)
With the high proportion of renewable energy through high-voltage direct current (HVDC) transmission into the grid and the application of high proportion of power electronic equipment, in the modern power system, the traditional electromagnetic conversion equipment represented by synchronous generators is gradually replaced by power electronic equipment, which in a high level has been affecting the dynamic behavior of the power system. In recent years, the wide-band oscillation problem of unknown mechanism continues to appear in power systems, which poses a major threat to the security, stability, and operation of power systems. Therefore, based on the typical oscillation event, this paper constructs a typical small-signal model of the new power system which is composed of synchronous generator, HVDC transmission equipment, and renewable energy generation equipment. The model is suitable for the analysis of wide-band oscillation problem of the new power system with renewable energy as the main body. The comparison of time-domain response with the detailed time-domain model shows that the proposed small-signal model can well reflect the dynamic behavior of the detailed time-domain model. Based on the model, the influence of access distance, access proportion, and operation and control modes of renewable energy integrated through LCC-HVDC on the wide-band oscillation characteristics of the system is analyzed, and the correctness of the analysis is verified by the detailed time-domain model.